Anatomizing the pulse: Edmund King's analogy, observation and conception of the tubular body. Issue 3 (3rd July 2022) - Huang, Yijie
ABSTRACT: In an unpublished anatomical treatise written around 1670, the English anatomist and fellow of the Royal Society of London Edmund King proposed that the human body was ultimately an assemblage of tubes and contained liquids. Without literally seeing every of its constituents to be tubular, how did King come to posit a tubular body? This article tackles the question by examining King's inquiry about the pulse against his framing of the circulatory system into a universally tubular model. Asking how King registered this model despite the limited visibility of vascularity in practice, I discuss the place of analogy in his anatomical observation. I argue that analogy constituted an essential strategy for extending what King had perceived to account for the hardly perceptible nuances of the human body. I concentrate on two of his analogies, in which the artery was compared to the cord and the ureter. These two analogies revealed remarkable epistemic potency in representing and reasoning the pulse as the inherent motion of the living artery. They suggest that in seventeenth-century observation accounts, analogy was not simply a rhetoric suspicious of violating the principle of scientific empiricism; rather, they opened up ways of seeing and imagining nature.